A multi-stage stochastic programming approach for supply chain risk mitigation via product substitution - Ghorashi Khalilabadi, Seyed Mahdi; Zegordi, Seyed Hessameddin; Nikbakhsh, Ehsan (Computers & industrial engineering, 2020)
•A case of pharmaceutical supply chains for livestock drug distribution is studied.•Partial product substitution is used for dealing with demand disruptions.•A multi-stage stochastic programming model is proposed to tackle the problem.•An improved progressive hedging algorithm is proposed to solve large instances.•Results shows the applicability of the method for dealing with demand disruption. Trends like globalization, shorter product life-cycles, and cost reduction strategies in the global business environment have exposed many supply chains to various risks. Disruptions are one of the supply chain risks that can interrupt product flow, delay customer deliveries, and reduce supply chain revenues considerably. Prior planning for disruptions could greatly alleviate these consequences. A method to cope with disruptions is to use product substitution in the case of a product shortage. In this research, the supply chain of a livestock-drug distribution company in Iran, facing demand disruptions, has been chosen as a case study. For this purpose, a multi-stage stochastic integer programming model is proposed and solved using a customized progressive hedging algorithm. Moreover, the effect of uncertainty on the supply chain performance is measured using the value of the stochastic solution (VSS) and the expected value of perfect information (EVPI) metrics. Based on the different instances of the problem solved, the VSS metric shows that modeling and solving the proposed stochastic model could enhance the company profit by about 3.27 percent on average. In addition, the EVPI metric demonstrates that planning and investing in proactive demand management could enhance the profit up to 9.42 percent. Finally, analyses indicate that when dealing with increased demand uncertainty levels, the importance of using the proposed method increases as the profitability of the company decreases.